Musik Gamelan di dalam Kekristenan Jawa yang menjadi Paradoks - Graha, Dwi Rendra (STT Bala Keselamatan Palu, 2025)
Abstract: Gamelan, as an integral part of Javanese cultural heritage imbued with philosophical and spiritual meaning, is often perceived as at odds with the universal principles of Christianity. However, in the context of Javanese Christianity, gamelan has been adapted and utilized as a liturgical instrument and a means of strengthening the religio-cultural identity of the community. This creates an interesting tension between local traditions and the teachings of the Christian faith. This paper aims to explore the role of gamelan in Christian practice among Javanese people, while also examining the dynamics of acceptance, resistance, and transformation processes that occur within the Javanese Christian community. Using a qualitative approach based on literature, this study finds that gamelan is not merely understood as a musical instrument, but also as a medium of inculturation that enriches Christian spiritual expression without abandoning its Javanese cultural roots. In conclusion, the integration of gamelan in Javanese Christian practice reflects the complexity of the interaction between religion and culture and demonstrates how the local context can engage in creative dialogue with the faith. Abstrak: Gamelan, sebagai bagian integral dari warisan budaya Jawa yang sarat dengan makna filosofis dan spiritual, kerap dipersepsikan berseberangan dengan prinsip-prinsip universal Kekristenan. Namun, dalam konteks Kekristenan Jawa, gamelan justru mengalami adaptasi dan difungsikan sebagai sarana liturgis serta penguatan identitas religio-kultural umat. Hal ini menciptakan suatu ketegangan yang menarik antara tradisi lokal dan ajaran iman Kristen. Tulisan ini bertujuan untuk mengeksplorasi peran gamelan dalam praktik kekristenan di kalangan masyarakat Jawa, sekaligus menelaah dinamika penerimaan, resistensi, dan proses transformasi yang terjadi di dalam komunitas Kristen Jawa. Dengan menggunakan pendekatan kualitatif berbasis studi pustaka, penelitian ini menemukan bahwa gamelan tidak sekadar dipahami sebagai instrumen musik, tetapi juga sebagai medium inkulturasi yang memperkaya ekspresi spiritual Kristen tanpa menanggalkan akar kebudayaan Jawa. Kesimpulannya, integrasi gamelan dalam praktik Kekristenan Jawa mencerminkan kerumitan interaksi antara agama dan budaya, serta menunjukkan bagaimana konteks lokal mampu berdialog secara kreatif dengan iman yang dianut.